Variations in the rancid-flavor compounds of human breastmilk under general frozen-storage conditions - Hsiao-Ying Hung; Yu-Yun Hsu; Pei-Fang Su; Ying-Ju Chang (BMC, 2018)
Abstract Background Human breastmilk provides the best nutrition for infants. When women or infants have difficulties in breastfeeding directly, breastmilk is usually pumped and frozen for later use. However, while frozen, breastmilk may develop a rancid flavor, which induces infant feeding stress and raises the mothers' concerns about the quality of frozen breastmilk. Nevertheless, few studies have investigated the variations in the compounds that cause the rancid flavor of breastmilk during frozen storage. Methods A repeated-measures design was adopted to quantify the variations in rancid-flavor compounds, namely acid value (AV), total free fatty acids (FFAs), and short-and intermediate-chain FFAs of breastmilk during frozen storage. Breastmilk was obtained from ten healthy mothers of full-term infants and each milk sample was divided into three aliquots: fresh, 7-day frozen and 30-day frozen samples. The fresh samples were immediately analyzed, while the others were frozen in a domestic fridge within a temperature range of −15 to −18 °C and analyzed 7 and 30 days later. Results The rancid-flavor compounds of the breastmilk, namely AV, total FFAs and intermediate-chain FFAs, significantly increased with storage time, all of which reached the sensory threshold for detecting the rancid flavor of milk. In addition, the FFAs of the breastmilk samples frozen for 7 days far exceeded the detection threshold for unpleased rancid flavor, while the 30-day samples were higher than the intolerable level for most people. Conclusions This study revealed that the human breastmilk develops a rancid flavor during frozen storage. Therefore, we recommend that when infants refuse thawed milk, mothers can try to provide freshly expressed milk whenever possible or provide breastmilk frozen for less than 7 days. Future studies could explore the methods for slowing breastmilk lipolysis to maintain its fresh flavor.